2019
DOI: 10.1007/s12182-019-00401-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-spherical particle mixing behaviors by spherical inert particles assisted in a fluidized bed

Abstract: Fluidized beds are widely used in many industrial fields such as petroleum, chemical and energy. In actual industrial processes, spherical inert particles are typically added to the fluidized bed to promote fluidization of non-spherical particles. Understanding mixing behaviors of binary mixtures in a fluidized bed has specific significance for the design and optimization of related industrial processes. In this study, the computational fluid dynamic-discrete element method with the consideration of rolling fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Consequently, there was an accumulation of solid particles in the reactor, which resulted in fluidization challenging of low contacting between gas and solid particle. [ 23,24 ] Hence, the existing design did not facilitate efficient gas–solid mixing and effective fluidization of the bed material.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, there was an accumulation of solid particles in the reactor, which resulted in fluidization challenging of low contacting between gas and solid particle. [ 23,24 ] Hence, the existing design did not facilitate efficient gas–solid mixing and effective fluidization of the bed material.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the biomass mixed well with the sand at high gas velocities. Ren et al 33 simulated the binary fluidization process of spherocylinders and spheres. They found that the addition of spherical particles made the spherocylinders tend to orient vertically.…”
Section: Introductionmentioning
confidence: 99%